2020
DOI: 10.1016/j.jhep.2020.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Beta-amyloid deposition around hepatic bile ducts is a novel pathobiological and diagnostic feature of biliary atresia

Abstract: Bulk transcriptome analysis Observations Validations Highlights Liver organoids from patients with BA exhibited aberrant morphology and disturbed apical-basal organization. Transcriptomic analysis of BA organoids revealed a shift from cholangiocyte to hepatocyte transcriptional signatures. Beta-amyloid accumulation was observed around the bile ducts in BA livers. Exposure to beta-amyloid induced aberrant morphology in control organoids. Beta-amyloid accumulation represents a novel finding with pathobiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 47 publications
4
56
0
Order By: Relevance
“…Functionally damaging variants included all protein-truncating variants and all missense or inframe coding variants that were predicted by SIFT as “deleterious”, by PolyPhen2 as “probably damaging” or that had a CADD score ≥ 20. Candidate gene mRNA and protein expression in liver or bile duct tissue were checked using the human tissue expression database in EMBL-EBI Expression Atlas ( www.ebi.ac.uk ) and our in-house BA liver organoid expression database [19] . The resulting rare, damaging biallelic variants were visually checked using Integrative Genomics Viewer (IGV).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally damaging variants included all protein-truncating variants and all missense or inframe coding variants that were predicted by SIFT as “deleterious”, by PolyPhen2 as “probably damaging” or that had a CADD score ≥ 20. Candidate gene mRNA and protein expression in liver or bile duct tissue were checked using the human tissue expression database in EMBL-EBI Expression Atlas ( www.ebi.ac.uk ) and our in-house BA liver organoid expression database [19] . The resulting rare, damaging biallelic variants were visually checked using Integrative Genomics Viewer (IGV).…”
Section: Methodsmentioning
confidence: 99%
“…Human foreskin fibroblast cells (BJ, CRL-2522; ATCC) were cultured in DMEM with 10% fetal bovine serum (FBS) and penicillin (100 IU/mL) and streptomycin (100 µg/mL) (Invitrogen). Human intra-hepatic cholangiocytes were derived from liver biopsy via the generation of bile duct organoids following our previously published protocol [19] . Human cholagniocytes were cultured as a monolayer on cover slip coated with Matrigel (356231; Corning Biocoat) in organoid medium until ready for short interfering RNAs (siRNA) transfection.…”
Section: Methodsmentioning
confidence: 99%
“…So far, Babu et al reported that cell junction defects were observed in BA patients and cultured cholangiocyte spheres 44 , while the correlation between these defects and BA development remains unknown. Gene sequencing analysis has suggested that genes associated with tight junctions and adherens junctions are enriched in aberrantly expressed gene sets 45 ; however, to the best of our knowledge, we have reported in detail for the first time that tight junctions and polarity complexes between parenchymal liver cells, including hepatocytes and cholangiocytes, are severely disrupted in BA livers.…”
Section: Discussionmentioning
confidence: 99%
“…Human foreskin fibroblast cells (BJ, CRL-2522; ATCC) were cultured in DMEM with 10% fetal bovine serum (FBS) and penicillin (100 IU/mL) and streptomycin (100 mg/mL) (Invitrogen). Human intra-hepatic cholangiocytes were derived from liver biopsy via the generation of bile duct organoids following our previously published protocol [19]. Human cholagniocytes were cultured as a monolayer on cover slip coated with Matrigel (356231; Corning Biocoat) in organoid medium until ready for short interfering RNAs (siRNA) transfection.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%